IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN PALU SELATAN KOTA PALU - Meiske, Meiske (Katalogis, 2015)
The purpose of this study is to investigate and provide a clear description of the implementation of the Family Hope Program in South Palu Sub-district. This research also aims at determining the factors that affect the program implementation. The type of this research is qualitative with descriptive approach. The research question is how the implementation of Family Hope Program in South Palu district. The informants were taken by using purposive sampling technique carefully so that they are relevant to the research structures, in which the sample was chosen according to the specific characteristics and particular characteristics, as many as 14 people. The data analysis is done through data reduction, data presentation and conclusion. The theory used is sourced from George C. Edwards III to determine the factors that influence implementation including communications, resources, executive attitudes (disposition) and bureaucratic structure. The results of this research indicate that the implementation variables (communication, resources, executive attitudes and bureaucratic structure) affect the implementation of the Family Hope Program in South Palu district either partially or simultaneously. There are other factors which affect the implementation of the Program, they are: the role of the companions and operators, coordination among institutions / agencies as well as budget / funding operational support. The research results show that the implementation of the program was implemented well although there were some obstacles due to weak coordination among institutions at the institutional level of Palu and among institutions / agencies in Central Sulawesi province to the central government but in general the Program in Palu Sub-district still runs dynamically and specifically the essence of the implementation namely the provision of health and education services to RTSM / KSM PKH participants carried out well and gone in a good manner.